Action sets and decisions in the medial frontal cortex. - Rushworth, M; Walton, M; Kennerley, S; Bannerman, D (2004)
Activations in human dorsomedial frontal and cingulate cortices are often present in neuroimaging studies of decision making and action selection. Interpretations have emphasized executive control, movement sequencing, error detection and conflict monitoring. Recently, however, experimental approaches, using lesions, inactivation, and cell recording, have suggested that these are just components of the areas' functions. Here we review these results and integrate them with those from neuroimaging. A medial superior frontal gyrus (SFG) region centred on the pre-supplementary motor area (pre-SMA) is involved in the selection of action sets whereas the anterior cingulate cortex (ACC) has a fundamental role in relating actions to their consequences, both positive reinforcement outcomes and errors, and in guiding decisions about which actions are worth making.